The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/978-3-642-23774-4_40
|View full text |Cite
|
Sign up to set email alerts
|

Are First Impressions about Websites Only Related to Visual Appeal?

Abstract: This paper investigates whether immediate impression about websites influences only perceptions of attractiveness. The evaluative constructs of perceived usability, credibility and novelty were investigated alongside visual appeal in an experimental setting in which users evaluated 20 website screenshots in two phases. The websites were rated by the participants after viewing time of 500 ms in the first phase and with no time limit in the second. Withinwebsite and within-rater consistency were examined in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Moreover, the model suggests that aesthetic elements are not the only determinants in establishing a favorable first impression. This observation has also been made by Papachristos and Avouris [93], who note that immediate impression about websites does not just influence perceptions of attractiveness.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, the model suggests that aesthetic elements are not the only determinants in establishing a favorable first impression. This observation has also been made by Papachristos and Avouris [93], who note that immediate impression about websites does not just influence perceptions of attractiveness.…”
Section: Discussionsupporting
confidence: 70%
“…First impressions have earlier been studied e.g. in the context of Web design, however focusing on very short exposure times (500ms and less) [16,22].…”
Section: First Impressions Vs Field Study Resultsmentioning
confidence: 99%
“…Lindgaard et al [25] noted that 'visual appeal clearly dominates first impression judgments of other characteristics such as perceived usability and trustworthiness. Judgments about credibility of websites were found less consistency but noteworthy between extremely short and long exposure [37]. From their experiment aesthetics were moderately correlated with credibility in both phases (r=.580 and r=.484).…”
Section: Trust and Aestheticsmentioning
confidence: 91%
“…Those experiments broaden our knowledge regarding how (fast) trust is formed during our first impression as Lindgaard et al [25] showed that people are able to judge the visual appeal, trust and usability of websites consistently upon viewing them only for 50 msec. Additionally, Papachristos and Avouris [37] showed how consistent these judgments are over time (after viewing 500 msec in the first phase and no time limit in the second phase). The above mentioned work shows already the relevant connection of visual aesthetics and trust.…”
Section: Trust and Aestheticsmentioning
confidence: 95%
See 1 more Smart Citation